MATHEMATICS MISCONCEPTIONS OF GEOMETRY MATERIALS IN PROSPECTIVE MATHEMATICS TEACHER STUDENTS - Purwaningrum, Jayanti Putri; Purwoko, Riawan Yudi (Euclid, 2023)
The research analyzes mathematical misconceptions about geometry material among prospective mathematics teacher students. This research uses a descriptive qualitative approach with a case study type. The research subjects were the Mathematics Education department students at Universitas Muria Kudus. Subjects were selected purposively by considering input from the Capita Selecta of Mathematics course teachers. Determining research subjects is based on test results on geometry material, which contains misconception schemes. The data collection method is through geometry material tests and interviews. Data analysis in this research was carried out in stages, including data reduction, data presentation, and drawing conclusions and verification. The research results show that misconceptions about geometry material are often found among prospective mathematics teacher students. Misconceptions in the geometric material of flat shapes, namely misconceptions in the definition related to the concept of parallelism and the relationship between the sub-materials of squares, rectangles, parallelograms, rhombuses, and kites. Misconceptions also arise when defining a right-angled trapezoid and determining the height of an obtuse triangle. Then, there are misconceptions about the sub-material of spatial shapes, namely the definition of tubes, cones, and pyramids. Misconceptions cause misconceptions, which are generally related to everyday meaning and practicality in explaining concepts.